Public opinion, the Press, and the failed Anglo-Franco-Soviet negotiations of 1939 - Hucker, Daniel (Taylor & Francis (Routledge), 2017)
For nearly 80 years, historians have debated whether the western powers or the USSR should be blamed for the failure of the Anglo-Franco-Soviet negotiations in 1939. This rather tired debate features here, but only in the background. Instead, these negotiations provide a case study for exploring the interface between the press, public opinion, and foreign policymaking, identifying an example of how policymakers’ perceptions of popular opinion wielded a tangible impact on diplomacy. The article will show that, from late April through to early June 1939, British and French public opinion, as mediated by the press, demanded a ‘Grand Alliance’. The popular pressure needed to facilitate a Soviet alliance was in place, and, combined with broader diplomatic and strategic imperatives, nearly delivered one. Perceptions of public opinion also help explain why this alliance remained elusive. Emboldened by their own readings of western newspapers, the USSR increased their demands, confident that domestic pressures would compel London and Paris to yield. But this was a fatal miscalculation. From mid-June, Western opinion turned against Moscow, and familiar anti-Soviet tropes resurfaced. By charting this evolution in public sentiment, this article provides a fresh perspective on the factors contributing to the failure of these negotiations.